Reading engagement of Indonesian secondary EFL teachers as literacy indicators perceived over reading resources and pleasure reading - Utami Widiati; Tengku Intan Suzila Tengku Sharif; Lina Hanifiyah; Meyga Agustia Nindya (Indonesian Journal of Applied Linguistics, 2023)
Nurturing students to become engaged readers for literacy development may need teachers who can play roles as models of keen readers. This descriptive quantitative study aims to profile the reading engagement of Indonesian EFL teachers as perceived from reading resources and pleasure reading. This study employed a survey questionnaire, requesting the respondents to reflect on their personal and school reading collection and their habits in reading for pleasure. Through a convenience sampling technique, voluntary responses were received from 183 secondary EFL teachers, mostly from East Java Province. The data were descriptively tabulated to result in frequencies and percentages. Research tool SPSS ver.24 was used to analyze the raw data for means, correlations, and compared means. Overall, this study found that reading engagement among secondary EFL teachers reflects moderately positive directions. The statistical analyses demonstrate that possessing personal reading resources may result in a slightly significant impact in assuring EFL teachers to read for pleasure yet better than having school reading resources. It has also been proven that both types of reading resources are weakly, yet significantly, correlated with reading for pleasure. This means that the more EFL teachers have access to reading resources, the more they will read and indirectly improve themselves. Future research may uncover the implications of having teachers engaged in reading on the design of more responsive reading instruction for the development of literacy culture at schools.